Squat jump training at maximal power loads vs. heavy loads: effect on sprint ability - Harris, N. K.; Cronin, J. B.; Hopkins, W. G.; Hansen, K. T. (The Journal of Strength and Conditioning Research, 2008)
Training at a load maximizing power output (Pmax) is an intuitively appealing strategy for enhancement of performance that has received little research attention. In this study we identified each subject's Pmax for an isoinertial resistance training exercise used for testing and training, and then we related the changes in strength to changes in sprint performance. The subjects were 18 well-trained rugby league players randomized to two equal-volume training groups for a 7-week period of squat jump training with heavy loads (80% 1RM) or with individually determined Pmax loads (20.0-43.5% 1RM). Performance measures were 1RM strength, maximal power at 55% of pretraining 1RM, and sprint times for 10 and 30 m. Percent changes were standardized to make magnitude-based inferences. Relationships between changes in these variables were expressed as correlations. Sprint times for 10 m showed improvements in the 80% 1RM group (-2.9 +/- 3.2%) and Pmax group (-1.3 +/- 2.2%), and there were similar improvements in 30-m sprint time (-1.9 +/- 2.8 and -1.2 +/- 2.0%, respectively). Differences in the improvements in sprint time between groups were unclear, but improvement in 1RM strength in the 80% 1RM group (15 +/- 9%) was possibly substantially greater than in the Pmax group (11 +/- 8%). Small-moderate negative correlations between change in 1RM and change in sprint time (r [almost equal to] -0.30) in the combined groups provided the only evidence of adaptive associations between strength and power outputs, and sprint performance. In conclusion, it seems that training at the load that maximizes individual peak power output for this exercise with a sample of professional team sport athletes was no more effective for improving sprint ability than training at heavy loads, and the changes in power output were not usefully related to changes in sprint ability.